A study of Sophocles' Oedipus Coloneus - Murphy, Jeanne Thomas (My University, 1957)
It is the intention and purpose of this thesis to study the Oedipus Coloneus of Sophocles. Since there is a real need for an investigation of the Coloneus as a work of art and not as a philosophical treatise or a theological tract, the limitations of my study are strictly defined. I shall direct my attention to the Coloneus, and the Coloneus only, and I do not intend to consider it either as a part of any "developmental" theory of the Sophoclean canon or as a document of any over-all Sophoclean "philosophy of life." No doubt the poet had something to say about human existence in his play, but I have made no effort to fit this into any hypothetical "system" that he may have had.
Thesis (M.A.)--University of Washington, 1957
Keywords: Thesis--Greek